Anastomotic Technique—How to Optimize Success and Minimize Leak Rates - Man, Jeannette; Hrabe, Jennifer (Clinics in Colon and Rectal Surgery, 2021)
Determining when to perform a bowel anastomosis and whether to divert can be difficult, as an anastomosis made in a high-risk patient or setting has potential for disastrous consequences. While the surgeon has limited control over patient-specific characteristics, the surgeon can control the technique used for creating anastomoses. Protecting and ensuring a vigorous blood supply is fundamental, as is mobilizing bowel completely, and employing adjunctive techniques to attain reach without tension. There are numerous ways to create anastomoses, with variations on the segment and configuration of bowel used, as well as the materials used and surgical approach. Despite numerous studies on the optimal techniques for anastomoses, no one method has prevailed. Without clear evidence on the best anastomotic technique, surgeons should focus on adhering to good technique and being comfortable with several configurations for a variety of conditions.
Keywords: bowel anastomosis; anastomotic technique; tension-free anastomosis; anastomotic leak